DIAGNOSTIC MODALITIES, MANAGEMENT, AND OUTCOMES OF BLUNT ABDOMINAL TRAUMA: A PROSPECTIVE OBSERVATIONAL STUDY AT A TERTIARY CARE CENTER (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Blunt abdominal trauma (BTA) is a major contributor to morbidity and mortality worldwide, particularly in developing countries where road traffic accidents are increasing. Prompt diagnosis using appropriate imaging techniques and timely therapeutic intervention are crucial for improving patient outcomes. This study aimed to evaluate the diagnostic modalities, management approaches, and clinical outcomes among patients presenting with blunt abdominal trauma at a tertiary care institution. Methods: A hospital-based observational descriptive study was conducted among 100 patients admitted with blunt abdominal trauma to the Department of General Surgery, Father Muller Medical College and Hospital, Mangalore, India, over an 18-month period from October 2022 to April 2024. Data regarding mechanism of injury, clinical presentation, diagnostic investigations, treatment strategies, and outcomes were collected and analyzed. Categorical variables were analyzed using Chi-square and Fisher’s exact tests, with statistical significance set at p < 0.05. Results: Most patients were male (83%), with the highest incidence in the 21–30-year age group (21%). Road traffic accidents were the leading cause of injury (68%). The liver was the most frequently affected organ (40%), followed by the spleen (29%). All patients underwent ultrasonography and contrast-enhanced computed tomography. Conservative management was successful in 75% of cases, whereas 25% required surgical intervention. The overall survival rate was 90%, while the mortality rate was 10%. The highest procedure-specific mortality was observed in patients undergoing exploratory laparotomy with ileostomy (60%), whereas conservatively managed patients demonstrated the lowest mortality (4%). Conclusion: Non-operative management is a safe and effective treatment option for hemodynamically stable patients with solid organ injuries resulting from blunt abdominal trauma. This approach is associated with lower mortality rates and shorter hospital stays compared to operative management.